2004
DOI: 10.1111/j.1439-0264.2004.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxytalan Fibres in the Periodontal Ligament of Equine Molar Cheek Teeth

Abstract: The distribution and arrangement of oxytalan fibres were examined in periodontal specimens of cheek teeth from seven horses. Oxidation prior to aldehyde fuchsin exposition permitted a selective staining of the oxytalan fibres, which are a distinct component of the elastic fibre system. On three horizontal levels of the periodontium--(a) subgingival, (b) middle third and (c) apical--two oxytalan fibre groups were shown histologically: 'blood vessel-related' and 'independent' oxytalan fibres. In levels a and b, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…An anti-Adamtsl6 polyclonal antibody was labeled with Alexa 488 by using the Zenon antibody labeling kit according to the manufacturer's instructions (Invitrogen) for double immunostaining with an anti-fibrillin-1 polyclonal antibody. For visualization of oxytalan fibers, sections were oxidized for 15 min in 10% Oxone (Merck) and subsequently stained with aldehyde fuchsin as described previously (20). Fluorescence images were sequentially collected using a confocal microscope featuring 403-, 488-, and 543-nm laser lines (LSM510; Carl Zeiss MicroImaging, Jena, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…An anti-Adamtsl6 polyclonal antibody was labeled with Alexa 488 by using the Zenon antibody labeling kit according to the manufacturer's instructions (Invitrogen) for double immunostaining with an anti-fibrillin-1 polyclonal antibody. For visualization of oxytalan fibers, sections were oxidized for 15 min in 10% Oxone (Merck) and subsequently stained with aldehyde fuchsin as described previously (20). Fluorescence images were sequentially collected using a confocal microscope featuring 403-, 488-, and 543-nm laser lines (LSM510; Carl Zeiss MicroImaging, Jena, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…ADAMTSL6β and fibrillin-1-positive microfibrils (green yellow) was markedly increased in the aorta and skin of TSL6β TG mice compared with WT mice. Bar ¼ 50 μm Image from published paper [39] Since oxytalan fiber, a principal elastic fiber system of PDL is composed of fibrillin-1 microfibrils and does not contain significant amounts of elastin [44,45], this composition suggests that PDL will have an increased susceptibility to breakdown in MFS compared with other elastic tissues composed of both elastin and fibrillin-1 [46]. We demonstrated that ADAMSL6β is highly expressed in DF during PDL forming stage.…”
Section: Adamtsl6β Involved In Pdl Formation and Repairmentioning
confidence: 90%
“…Oxytalan fi bers are composed of 10-12 nm wide microfi brils without any amorphous elastin substance. They are oriented in an occluso-apical direction and topographically related to the periodontal vascular system [ 49 ]. Elaunin fi bers may also be found in association with fi ber bundles in the gingival ligament.…”
Section: Composition and Structure Of Periodontal Ligamentmentioning
confidence: 99%